The pitfalls of ectomycorrhizal microcosms: lessons learnt for future success - André Geremia Parise; Vinicius Henrique De Oliveira; Mark Tibbett; Brian John Pickles (Plant Signaling & Behavior, 2025)
Mycorrhizal fungi are known to support their host plants by facilitating nutrient acquisition and enhancing resistance to biotic and abiotic stress. However, the possibility that they also convey structural information about the soil has not yet been tested. Here, we attempted to investigate whether ectomycorrhizal hyphae could guide root growth in response to physical obstacles by using Scots pine (Pinus sylvestris) and Suillus granulatus in a microcosm experiment fitted with U-shaped silicone mazes. Despite initial success in achieving ectomycorrhizal colonisation (88% of the inoculated seedlings), the fungi failed to produce the expected hyphal networks. Extensive and unexpected root growth rendered the system unsuitable for testing our hypothesis. Furthermore, structural issues with the microcosms compromised substrate integrity, possibly inhibiting fungal development. While our results were inconclusive, this report highlights challenges associated with replicating classical ectomycorrhizal experiments, underscoring the need for methodological refinement. We provide detailed recommendations and methodological clarifications that may aid future research. Although our initial hypothesis could not be tested, we argue that traditional microcosm experiments retain potential for advancing our understanding of mycorrhizal ecology, provided they are critically revisited and technically improved. Negative results, when well contextualised, are valuable contributions toward more robust and reproducible experimental frameworks.